Environmental footprint quantification and optimization methods for digital poster design based on life cycle assessment - Yilin Liu; Ping Ji (PLoS ONE, 2026)
Digital poster design has become a dominant visual communication medium, yet its environmental impacts remain poorly understood despite assumptions of inherent sustainability. This research developed a specialized life cycle assessment methodology to quantify and optimize the environmental footprint of digital poster systems. The framework encompasses five lifecycle stages from design creation through data deletion, employing real-time monitoring and dynamic data collection across a six-month case study with a digital marketing agency. Assessment results revealed total carbon emissions of 7.45 kg CO₂-eq per functional unit, with distribution infrastructure and display operations contributing 89% of lifecycle impacts. Implementation of comprehensive optimization strategies achieved 28.6% reduction in climate change impact through hardware efficiency improvements, temporal scheduling, and cloud platform adoption. Sensitivity analysis identified data center PUE as the most influential parameter, while geographic variations significantly affected regional impacts. The methodology advances LCA application in digital systems by incorporating workload-specific assessments and providing actionable optimization guidance. These findings demonstrate that systematic environmental management can achieve substantial impact reductions while maintaining creative excellence, supporting the digital design industry’s transition toward genuine sustainability rather than merely shifting environmental burdens between lifecycle stages.